Effects of space weather on the ionosphere: A case study of geomagnetic storms during 17-28 February 2014 - Aol, Sharon; Mungufeni, Patrick; Jurua, Edward (Indian Journal of Radio & Space Physics, 2020)
This study focused on the effects of space weather on the ionosphere during geomagnetic storms for the period 17-28 February 2014 over the African low, latitude region. The Global Positioning System (GPS) data, derived from dual frequency receivers installed along the African low, latitude were analyzed to get Total Electron Content (TEC) and this was used to study the response of the ionosphere to the geomagnetic storms. Positive and negative ionospheric storm effects were observed during the period of study. These geomagnetic storm effects were discussed in terms of the Prompt Penetration Electric Field (PPEF) storm induced wind lifting effect and Disturbance Dynamo (DD) electric field. Although these storms occurred during the same period, their impacts and associated features on the ionosphere varied due to different contributing factors to their driving mechanisms. A shift in equatorial VTEC enhancement from one GPS station to another was observed, showing a longitudinal dependence of the ionospheric response to the geomagnetic storms and this was attributed to composition changes. In addition, Rate of Change of TEC Index (ROTI) was used to examine the occurrence of ionospheric irregularities. Out of all the storms studied, the storms on 19 and 20 February 2014, inhibited the occurrence of ionospheric irregularities, while the remaining storms triggered ionospheric irregularities. The generation of post-sunset irregularities was attributed to the Rayleigh Taylor Instability mechanism. A longitudinal dependence of the enhancement/inhibition of ionospheric irregularities was also observed.
Keywords: Space weather; Geomagnetic storms; Ionospheric disturbances